In-Operando Neutron Diffraction Investigation of Structural Transitions during Lithiation of Si Electrode in Li-Ion Battery. Issue 10 (1st October 2022) - Srinivasan, R.; Chandran, K. S. Ravi; Chen, Y.; An, K.
Abstract : A major challenge for Si negative electrodes in Li-ion batteries is how to accommodate the large lithiation-induced volume expansion and prevent electrode fragmentation, such that impressive Li storage capacity of Si can be exploited in practice. Electrochemically etched Si mesoporous electrodes have significant potential in this context. This research is focused on an optimum mesoporous Si electrode structure that shows a very high energy storage density, electrochemically cycling well without cracking or fragmentation. To explore the factors causing the superior performance, this study performed in-operando neutron diffraction experiments on optimized electrode during lithiation-delithiation cycles in a simple in-situ electrochemical cell. It is shown that an unusual diffraction phenomenon arises from lithiation-induced expansion of Si leading to the development of mosaic structure in Si. This new phenomenon appears to arise from the increased contribution of kinematic diffraction from the lithiated Si, relative to the conventional dynamic diffraction. This is also supported by changes in diffraction intensities directly synchronizing with the volume changes in Si during lithiation-delithiation cycle. The in-operando experiments explain why the optimum mesoporous Si electrode possesses a high specific capacity without electrode fragmentation. The present findings can help to improve Si electrode designs for high energy density Li-ion batteries.